Prevalence of Tendinopathy of the Gastrocnemius Muscle Origin in a Cohort of Sound Border Collies - Vannini, Rico; Ebling, Alessia Joan; Spattini, Giliola; Kowaleski, Michael P. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
This study aims to report the findings of the clinical examination, gait analysis, radiographs and ultrasonographic examination of the gastrocnemius tendon of origin in sound Border Collies. This study also aims to determine if this tendinopathy could be present in isolated individuals without signs of an overt lameness.A cohort of Border Collies, active participating in agility without a history of rear limb lameness were included in the study. A standardized general orthopaedic examination was performed in each dog with special attention given to the gastrocnemius muscle and its tendon of origin. An additional gait analysis was performed for further information about loading of each limb. Mediolateral radiographs of both stifle joints were taken to assess joint health and an ultrasound was performed to evaluate the origin of the gastrocnemius tendon.34 Border Collies were included in the study. Eighteen dogs had abnormal findings during clinical examination of the of the origin of the gastrocnemius tendon. All of these dogs also had abnormal findings on ultrasound, with six of them also having mineralization surrounding the fabellae on radiographs. Only four dogs had normal clinical, radiographic and ultrasonographic findings.This study supports our clinical impression that tendinopathy of the gastrocnemius muscle is likely an underestimated disorder in Border Collies that actively participate in agility.
Keywords: gastrocnemius; tendinopathy; agility; Border Collies; sports injury